Determinant Factors of Low Birth Weight in Loa Janan District: A Retrospective Cohort Study - Ratnawati, Ratnawati; Toaha, Aminah; Ginting, Riska Mayang Saputri (Poltekkes Kemenkes Palu, 2023)
In Samarinda in the Loa Janan Ilir sub-district, 8.23% (93 cases) of babies were born with low birth weight in 2021, two times from the previous year. The research is needed to understand the risk factors of LBW during pregnancy, such as anemia, chronic energy deficiency (CED) and the appropriateness of weight gain, in order to determine prevention programs. This study used a retrospective cohort method by looking at exposure during pregnancy and the baby's birth weight. The data used in this research is secondary data using a total sampling technique on the population of mothers who gave birth from January to May 2023. Analysis was carried out by looking at causal relationships and relative risk (RR) using the Chi-Square test and multivariate logistic regression. There was no relationship between anemia (p-value= 0.634) dan CED (p-value= 0.794) and appropriate weight gain (p-value= 0.189) during pregnancy and the incidence of LBW. Based on a multivariate test, it was found that pregnant women < 20 years old had a 45.16 times greater risk of having a LBW child (p=0.017). Meanwhile, mothers with inappropriate weight gain have a 7.6 times risk of having LBW children compared to those with (p-value=0.054). This is likely to occur because the majority of pregnant women have applied double doses to anemic pregnant women, but have not yet determined the adequacy of maternal’s diet based on inadiquate weight. Community health center is expected to carry out behavioral change interventions related to diet during pregnancy, apart from the importance of consuming supplements, as well as education regarding the impact of adolescent pregnancy.